Enterotomy covered with ileocecal ligament in an equine: case report - Gómez D., Gabriel (2020)
The case of a three-year-old Thoroughbred female horse with acute abdominal syndrome related to an irreducible, swollen and swollen umbilical hernia, which was referred to surgery is reported. During the surgical procedure a necrotic adhesion was detected in the antimesenteric part of a segment of the ileum. In order to remove the affected portion, an enterotomy was performed, which was reinforced by transposition of the ileocecal ligament to avoid stenosis or the possible collapse of the anastomotic line. The results of the surgery were satisfactory, and the patient evolved favourably.